Analisis Sistem Pelayanan Administrasi salam Penerimaan Pasien BPJS Di Ruang Instalasi Gawat Darurat Rumah Sakit Umum Daerah Datu Pancaitana Kabupaten Bone - Andi Mu’tiah Sari (Universitas Muhamadiyah Manado, 2022)
The implementation of management system in health services is common as an attempt to improve the quality. In Indonesia, the most commonly used health insurance is the service issued by Badan Penyelenggara Jaminan Social or BPJS (Social Security Administration) that collaborates with many hospitals such as Datu Pancaitana Regional Public Hospital in Bone Regency. This research uses qualitative approach with a case study as the research design. The research data are obtained through in-depth interviews with The Head of Medical Records Department, some staffs of the administrative service as well as patients of BPJS users in the Emergency Unit. In addition to that, this research collects its research data through field observations and a review of related previous studies. The findings reveal that the hospital management applies the following strategies in the division of administrative services: (1) planning through trainings and workshops provided for the human resources as well as the formulation of RUK and RPK; (2) organising through trainings involving a number of institutions within Datu Pancaitana Regional Public Hospital in Bone Regency; (3) actuating through an execution of administrative services for BPJS users; (4) controlling through supervision facilitated by the hospital management; (5) evaluating that addresses the process of human resources quality promotion through databased information trainings. In conclusion, the findings of this research are hoped to provide insights that can be useful for the hospital management specifically the emergency unit to improve their performance in providing services for BPJS users. They can start by assessing the development and training, program execution and evaluation aspects as well as by improving the facilities and infrastructure.